BNF in grain legumes in LPJ-GUESS - Ma, Jianyong; Olin, Stefan; Anthoni, Peter; Rabin, S. Sam; Bayer, D. Anita; Nyawira, S. Sylvia; Arneth, Almut (2021)
This file contains the input data for model runs on global scale and the measured results for BNF evaluation at site scales presented in Geoscientific Model Development (GMD) paper